2013
DOI: 10.1093/eurjhf/hft026
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output response to exercise in relation to metabolic demand in heart failure with preserved ejection fraction

Abstract: AimsExercise intolerance is a hallmark of heart failure with preserved ejection fraction (HFpEF), yet its mechanisms remain unclear. The current study sought to determine whether increases in cardiac output (CO) during exercise are appropriately matched to metabolic demands in HFpEF. Methods and resultsPatients with HFpEF (n ¼ 109) and controls (n ¼ 73) exercised to volitional fatigue with simultaneous invasive (n ¼ 96) or non-invasive (n ¼ 86) haemodynamic assessment and expired gas analysis to determine oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
260
4
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 293 publications
(292 citation statements)
references
References 39 publications
22
260
4
6
Order By: Relevance
“…In summary, numerous recent studies have changed the way we conceptualize the pathophysiology of HFpEF: away from being simply a disorder of diastolic dysfunction to more of a global impairment in the multiple components of cardiovascular 15, 23 and peripheral 18,20 reserves, which limits the ability to cope with physiologic stresses such as exercise. Further research is required to refine our understanding, enabling more optimal treatment for patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, numerous recent studies have changed the way we conceptualize the pathophysiology of HFpEF: away from being simply a disorder of diastolic dysfunction to more of a global impairment in the multiple components of cardiovascular 15, 23 and peripheral 18,20 reserves, which limits the ability to cope with physiologic stresses such as exercise. Further research is required to refine our understanding, enabling more optimal treatment for patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…45 In a separate study, Abudiab et al noted that for any increase in LVEDP, the increase in cardiac output was markedly attenuated in patients with HFpEF compared to controls. 23 Clinically, this failure of the Frank-Starling reserve is most clearly manifest as an elevation in LVFP, and recent studies have provided insight into the pathogenesis of this process. Westermann et al performed conductance catheter analysis in 70 HFpEF patients and 20 controls, and observed both prolonged relaxation and increased diastolic elastance.…”
Section: Normal Exercise Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Santos et al 11 and Abudiab et al 12 suggested that the major contributor to exercise inability in HFpEF patients is the reduced cardiac output relative to metabolic needs, indicating a cardiac cause. Extensive fibrosis and titin hypophosphorylation 7 is thought to create stiffness in the LV of patients with HFpEF, contributing to the cardiac limitations in exercise capacity.…”
Section: Introductionmentioning
confidence: 99%